Joint Forest Management in Punjab - Singh, Gurmeet (Indian Forester, 2000)
Punjab is predominantly an agricultural state, the forest area being only 6%. This area has been divided into block forest, partly Govt. owned and part owned by private communities; and strip forest for the purposes of Joint Forest Management. The block forest include areas prone to severe soil erosion and degradation. Previous efforts to improve these areas did not meet with much success. Under JFM resolution, Forest Protection Committees were formed and given share in forest produce to meet their requirements. World Bank aided Project, 1995 improved management further under which committees were made responsible for maintaining plantations, given share in revenue and also planning. Punjab Afforestation Project further improved situation, in which villagers were given larger share in revenues. The comprehensive guidelines associated the people, including women in Management plan, which was more effective in conserving and improving the forests. The management of Strip forests associated adjoining landowners in protecting these forests and sharing revenues therefore these are making steady progress. These include roadside, canal side, plantation etc.